Gene expression in pathogenesis of Metarhizium anisopliae and two armyworm species using real time quantitative reverse transcription-PCR - Javar, Saeedeh (2012)
Study on expression timing of pathogenesis-related (PR) genes in pathogen and immunity-related (IR) genes in insect host will provide insights into enhancing the virulency of entomopathogenic fungi. This research was conducted on two armyworm species, Spodoptera exigua (Hübner) and S. litura (F.), due to their great economic impact especially in the tropical regions. An isolate of Metarhizium anisopliae was chosen from four local fungal isolates because it caused the highest mortality in both S. exigua (82.40%) and S. litura (61.11%) larvae and the lowest LT50 value in S. exigua (three days) and S. litura (five days). Armyworms were reared on Centella asiatica (pegaga) and the life cycles of the pests were characterized. The selected IR genes were encoded for lysozyme (LYZ) and prophenoloxidase (PPO), while the PR genes for subtilisin-like protease (PR1), chitinases (CHI2 and CHI3), and peptide synthetase (PES). Gene expression analyses were conducted during the different stages of M. anisopliae infection in S. exigua and S. litura larvae using quantitative real-time RT-PCR. Sampling were at 0, 2, 12, and 24 hours after infection, and during several stages including when the infected larvae reached the moribund stage, when white mycelium emerged from the insect cadavers, when few conidia had formed on the mycelium, and when the cadavers were mummified by the conidia. For comparison, pure conidia and mycelia harvested from culture media were also included. In general, the expression profiles of the IR genes were similar in both S. exigua and S. litura larvae, although PPO and LYZ were differentially expressed during the infection process. The expression level of LYZ was significantly increased at 24 hours after infection and at the moribund stage, signifying LYZ role in host protection. For PPO, slight differences were detected between the expression levels until 24 hours. However, PPO expression was suppressed when both insects’ larvae were at the moribund stage. Among the fungal PR genes, PR1 expression was detected early at 2 hours after infection and this level increased as infection progressed. CHI2 and CHI3 expressions were detected later, at 12 hours after infection and when mycelium emerged from cadavers, respectively. The expression levels of PR1, CHI2 and CHI3 genes increased significantly during the emergence of mycelium from the cadavers and at the beginning of conidiogenesis, but decreased at later stage. As expected, their expressions in pure fungal propagules were at very low levels. For PES gene, fold changes were not significant between different samples (less than one-fold), indicating this gene might not be important in pathogenesis. High expression levels of PR1, CHI2, and CHI3 genes during the emergence of mycelium from cadavers and at early stages of conidiogenesis clearly indicate the importance of these genes during M. anisopliae infection on armyworms.